Pendidikan Islam Berbasis Masyarakat Dalam Penguatan Toleransi Antar Umat Beragama Di Jalan Jepara RW 01 Surabaya - Ica Nuriyatuzzahro; Muhammad Arif Syihabuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Indonesia is a pluralistic nation with a diverse population in terms of religion, ethnicity, and culture. Amidst this diversity, religious tolerance plays a crucial role in maintaining social harmony. This study aims to explore the role of community-based Islamic education in fostering interfaith tolerance within the multireligious environment of Jalan Jepara RW 01, Surabaya. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings indicate that TPQ students demonstrate empathetic attitudes toward differences, which are reflected in their inclusive social interactions—such as not discriminating against peers based on religion and actively participating in interfaith social activities. The Islamic education provided not only focuses on religious cognitive aspects but also instills values of tolerance, appreciation for diversity, and a spirit of peaceful coexistence. This study contributes to the body of literature on Islamic education and pluralism by emphasizing the role of informal institutions such as TPQ as key agents in shaping tolerant character within diverse societies. Strengthening non-formal education in local contexts can be an effective strategy for enhancing social cohesion and reducing the potential for religion-based conflicts.